2014
DOI: 10.3390/ma7010471
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Properties of Surface Functionalized BaTiO3 Embedded in Poly(methyl methacrylate)

Abstract: As-received BaTiO3 nanopowders of average grain sizes 50 nm and 100 nm were functionalized by (3-aminopropyl)triethoxysilane (APTES) and mixed with poly(methyl methacrylate)/toluene solution. The nanocomposite solution was spin coated on Si substrates to form thin films. The photoluminescence spectrum of the pure powder was composed of a bandgap emission at 3.0 eV and multiple bands centered about 2.5 eV. Surface functionalization of the BaTiO3 powder via APTES increases overall luminescence at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The TPUs are located at 816, 1076-1103, 1221, 1310, 1414, 1530, 1597, 1701-1730, 2853-2938, and 3300-3728 cm −1 (Figure 6b). According to the studies reported thus far, the IR band of bending vibrational modes of N-H can be observed at 816 cm −1 , while the absorption bands from 1000-1150, 1202, 1597, and 3100-3600 cm −1 are attributed to the vibrational modes of stretching C(O)-OC, CO stretching in the ether group, C-C + C=C in the benzene ring, and the stretching vibrational modes of the NH group, respectively [38][39][40]. The IR bands of 2853 and 2938 cm −1 are attributed to the anti-symmetrical and symmetrical vibrational modes of the CH bonds, respectively [41,42].…”
Section: Morphological and Structural Properties Of The Composites Bamentioning
confidence: 88%
“…The TPUs are located at 816, 1076-1103, 1221, 1310, 1414, 1530, 1597, 1701-1730, 2853-2938, and 3300-3728 cm −1 (Figure 6b). According to the studies reported thus far, the IR band of bending vibrational modes of N-H can be observed at 816 cm −1 , while the absorption bands from 1000-1150, 1202, 1597, and 3100-3600 cm −1 are attributed to the vibrational modes of stretching C(O)-OC, CO stretching in the ether group, C-C + C=C in the benzene ring, and the stretching vibrational modes of the NH group, respectively [38][39][40]. The IR bands of 2853 and 2938 cm −1 are attributed to the anti-symmetrical and symmetrical vibrational modes of the CH bonds, respectively [41,42].…”
Section: Morphological and Structural Properties Of The Composites Bamentioning
confidence: 88%
“…For the BT–OH NPs, the shoulder band at 3510 cm −1 was assignable to the free hydroxyl groups, whereas the broad band centered at 3422 cm −1 was attributable to the stretching vibrations of the hydroxyl groups at the surfaces of the BT NPs. The intense band at 570 cm −1 was characteristic of the stretching vibrations of TiO bonds . A few bands at 2910, 1632, and 1426 cm −1 could result from the residues of the organic precursor of the BT NPs .…”
Section: Resultsmentioning
confidence: 99%
“…The intense band at 570 cm 21 was characteristic of the stretching vibrations of TiAO bonds. 45 A few bands at 2910, 1632, and 1426 cm 21 could result from the residues of the organic precursor of the BT NPs. 46 After the surfaces of the BT NPs were treated with APTES, new bands appeared at 1034, 1113, and 1575 cm 21 .…”
Section: Surface Functionalization Of Bt Npsmentioning
confidence: 99%
“…The energy band gap values of pure films and heterostructures estimated from their plots between (α h ν) 2 and ( h ν) (see Figure S3) are tabulated in Table . The band gap values of pure BTO and MoO 3 films are found to be 3.23 and 3.02 eV, respectively, and are in agreement with the literature. ,,, The band gap values of heterostructures lie in between the values of BTO and MoO 3 films and found to be maximum for the heterostructure with t MoO 3 = 67 nm. This can be attributed to the Burstein Moss shift caused by the distribution of free charge carriers across the heterojunction .…”
Section: Resultsmentioning
confidence: 99%